Implementing STACK questions concerning integration techniques combined with the usage of STACK in ILIAS - Rathmann, Wigand; Copado Mejías, Jesús (International STACK user group meeting (2. STACK Conference), 2019)

Sage als Content-Element in ILIAS nutzen - Rathmann, Wigand; Copado Mejías, Jesús (18. Internationale ILIAS-Konferenz, 2019)
Hands-on Tutorial Für ein besseres Verständnis helfen interaktive Inhalte weiter. Im Bereich der Statistik oder der Darstellung von dreidimensionalen Objekten fehlte bisher die Möglichkeit, dies direkt in Lernmodulen einzubinden. Mit dem neuen Content-Element "SageMath-Cell" kann nun z.B. direkt R-Code in Lernmodulen genutzt werden. SageMath ist ein mathematisches Softwaresystem, das die Nutzung vieler Open-Source-Pakete, wie Maxima oder R, zusammenfasst; es kann auch Python genutzt werden. In diesem Workshop wird an Beispielen erprobt, wie das Content-Element aus Autorensicht angewendet werden kann. Ihre Ideen können Sie gerne mitbringen – und bitte auch Ihren Compute

The NEMESIS Social Innovation Learning Platform - Protopsaltis, Aristidis; Copado Mejías, Jesús; Schorer, Antonia; Garefi, Ioana; Kalemaki, Irene (Proceedings of 11th International Social Innovation Research Conference, 2020)
This paper presents the NEMESIS Social Innovation Open Learning Platform (SIOLP) and its evaluation results during piloting in 5 European countries. The NEMESIS SIOLP is an open adaptive and evolving platform, based on ILIAS open source software, that ensures access to SI education for all. Existing educational programs on social innovation or on social entrepreneurship education are limited, while they cannot be accessed by all. Additionally , there is no platform that supports Social Innovation Education (SIE). The NEMESIS SIOLP offers the tools and resources to all teachers, trainers and educators around Europe to adopt the NEMESIS social innovation education model in an easy and effective way. The platform provides open access to useful resources for teachers but also an online knowledge sharing space for students. Particularly, For the evaluation of the NEMESIS SIOLP, a single-factor design has been used, using two different questionnaires during the pre-pilot evaluation. The System Usability Scale (SUS) developed by Brooke (1996) and the IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999). The SUS questionnaire was modified to include some more task specific questions to fit the NEMESIS tasks. The IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999) is a user-oriented approach to software evaluation and its short version was used. Additionally, a realistic approach was used during the pilot phase. A realistic approach to evaluation permits us to understand under what circumstances complex interventions work or fail (Pawson & Tilley, 2004). The results presented in this paper refer to the first complete evaluation of the “alfa” version of the system in 5 European counties and 8 schools. The survey was anonymous and the participants had to complete a set of tasks before they answered the questionnaire. The evaluation results have shown that the NEMESIS SIOLP largely supports the stakeholders' needs but usability issues were identified
Keywords: Social Innovation; Social Innovation Education; Open Learning Platform; Evaluation

The NEMESIS Social Innovation Open Learning Platform: An Evaluation - Protopsaltis, Aristidis; Copado Mejías, Jesús; Garefi, Ioana; Kalemaki, Irene; Kantsiou, Sofia (7th EMES International Research Conference on Social Enterprise 2019, 2019)
NEMESIS stands for New Educational Model Enabling Social Innovation Skills development and it is a Horizon 2020 project. It envisages the development of a new educational model that will harvest students’ knowhow and further build on their inherent competences as a means of improving their capabilities and drive social change. This process will enable students to become creative social thinkers, develop entrepreneurial mind-sets and become social change makers into a world where inequality, poverty and social exclusion are still quite evident. The NEMESIS approach is based on principles of participatory pedagogies focusing on collective learning and co-creation of new knowledge. NEMESIS introduces new relations and processes whereby students are empowered to create their learning paths during a process that emerges through participation and active engagement with others. To assist this process, the NEMESIS Social Innovation Open Learning Platform (SIOLP) has been developed. NEMESIS SIOLP is an open adaptive and evolving platform, based on ILIAS open source software, that ensures access to SI education for all. Existing educational programs on social innovation or on social entrepreneurship education are limited, while they cannot be accessed by all. Additionally, there is no platform that supports Social Innovation Education (SIE). The NEMESIS SIOLP offers the tools and resources to all teachers, trainers and educators around Europe to adopt the NEMESIS SIE model in an easy and effective way. The platform provides open access to useful resources for teachers but also an online knowledge sharing space for students. Particularly, the NEMESIS platform is offering access to: a) guides and training material for using the NEMESIS model, b) educational resources aiming at introducing Social Innovation philosophy and competences to students, c) access to the members of the Social Innovation Practitioners (SIP) community, d) and finally access to an online collaborative environment. The main features of the NEMESIS SIOLP include: a flexible Course Management for a multitude of didactical scenarios and study programs that allow the reproduction of full curriculums with a single tool. Additionally, content sharing with fast Drag & Drop File Upload, a personal workspace for learners, allowing the easy creation of blogs, simple creation of study materials with authoring tools such us build learning modules, wikis, glossaries, and much more. Furthermore, the platform enables a large number of integrated communication tools such as personal profiles, contacts, who is online?-tool, mail, chat and more. A general characteristic of the NEMESIS SIOLP is the ILIAS concept of Personal Desktop and Repository. While the Repository contains all content, courses and other materials structured in categories and described by metadata, the Personal Desktop is the individual workspace of each learner, author, tutor and administrator. The Personal Desktop contains selected items from the as well as certain tools like mail, tagging, a calendar and also e-portfolio and personal blogs. For the evaluation of the NEMESIS SIOLP a single-factor design has been used, using two different questionnaires. The System Usability Scale (SUS) developed by Brooke (1996) and the IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999). The SUS questionnaire is an effective tool for global assessing the system’s usability consisting of ten items. The SUS questionnaire was extended to include some more task specific questions to fit the NEMESIS tasks. The IsoMetrics usability inventory (Gediga, Hamborg & Düntsch, 1999) is user-oriented approach to software evaluation. The short version of the IsoMetrics inventory, which comprises 75 items, was used. Those items are aiming to operationalise the seven dialog design principles of the international standard ISO 9241-10: i) Suitability, ii) Self Descriptiveness, iii) Controllability, iv) Conformity with user expectations, v) Error Tolerance, vi) Suitability for individualization and vii) Suitability for learning. The results presented here refer to the first internal evaluation of the “alfa” version of the system. Twelve users took part in the survey. The survey was anonymous and the participants had to complete a set of tasks before they answered the questionnaire. The evaluation results have shown that the NEMESIS SIOLP largely supports the stakeholders’ needs by performing the tasks it was planned to perform, in a coherent and user-friendly way. The majority of participants found the platform easy to use, not complex at all and felt confident in using i

The NEMESIS Social Innovation Open Learning Platform: An Evaluation - Protopsaltis, Aristidis; Copado Mejías, Jesús; Garefi, Ioana; Kalemaki, Irene; Kantsiou, Sofia (ISIRC Book of Abstracts, 2019)